Measures for the prevention of ventilator-associated pneumonia - Costa, Francisca de Aquino Vieira (2022)
The objective of this study was to identify measures to prevent ventilator-associated pneumonia. This is a narrative literature review with a qualitative approach. The review arose from the concern “What are the preventive measures applied to ventilator-associated pneumonia?”. For this purpose, a search for studies was carried out in the Latin American and Caribbean Literature on Health Sciences database (LILACS), in the Google Scholar virtual search engine and in the virtual libraries Scientific Electronic Library Online (SciELO) and Virtual Health Library (BVS). Basic measures to prevent ventilator-associated pneumonia include reducing time on the ventilator; professional training regarding the management of mechanical ventilation; decrease in routine or scheduled changes in the ventilator circuit; preference for raising the head of the bed to 45º; maintenance of ideal cuff pressure (25-30 cmH2O or 18-22 mmHg) among other actions. The importance of following protocols, professional training, recommendations and bundles is highlighted, paying attention to the need for multidisciplinary actions that must be applied in daily care practice.